Immunometabolism of macrophages regulates skeletal muscle regeneration - Chen, Yu-Fan; Lee, Chien-Wei; Wu, Hao-Hsiang; Lin, Wei-Ting; Lee, Oscar K. (Frontiers in Cell and Developmental Biology, 2022)
Sarcopenia is an age-related progressive loss of skeletal muscle mass, quality, and strength disease. In addition, sarcopenia is tightly correlated with age-associated pathologies, such as sarcopenic obesity and osteoporosis. Further understanding of disease mechanisms and the therapeutic strategies in muscle regeneration requires a deeper knowledge of the interaction of skeletal muscle and other cells in the muscle tissue. Skeletal muscle regeneration is a complex process that requires a series of highly coordinated events involving communication between muscle stem cells and niche cells, such as muscle fibro/adipogenic progenitors and macrophages. Macrophages play a critical role in tissue regeneration and the maintenance of muscle homeostasis by producing growth factors and cytokines that regulate muscle stem cells and myofibroblast activation. Furthermore, the aging-related immune dysregulation associated with the release of trophic factors and the polarization in macrophages transiently affect the inflammatory phase and impair muscle regeneration. In this review, we focus on the role and regulation of macrophages in skeletal muscle regeneration and homeostasis. The aim of this review is to highlight the important roles of macrophages as a therapeutic target in age-related sarcopenia and the increasing understanding of how macrophages are regulated will help to advance skeletal muscle regeneration.